The next-generation sphingosine-1 receptor modulator BAF312 (siponimod) improves cortical network functionality in focal autoimmune encephalomyelitis - Hundehege, Petra (Neural Regen Res, 2019)
Autoimmune diseases of the central nervous system (CNS) like multiple sclerosis (MS) are characterized by inflammation and demyelinated lesions in white and grey matter regions. While inflammation is present at all stages of MS, it is more pronounced in the relapsing forms of the disease, whereas progressive MS (PMS) shows significant neuroaxonal damage and grey and white matter atrophy. Hence, disease-modifying treatments beneficial in patients with relapsing MS have limited success in PMS. BAF312 (siponimod) is a novel sphingosine-1-phosphate receptor modulator shown to delay progression in PMS. Besides reducing inflammation by sequestering lymphocytes in lymphoid tissues, BAF312 crosses the blood-brain barrier and binds its receptors on neurons, astrocytes and oligodendrocytes. To evaluate potential direct neuroprotective effects, BAF312 was systemically or locally administered in the CNS of experimental autoimmune encephalomyelitis mice with distinct grey- and white-matter lesions (focal experimental autoimmune encephalomyelitis using an osmotic mini-pump). Ex-vivo flow cytometry revealed that systemic but not local BAF312 administration lowered immune cell infiltration in animals with both grey and white matter lesions. Ex-vivo voltage-sensitive dye imaging of acute brain slices revealed an altered spatio-temporal pattern of activation in the lesioned cortex compared to controls in response to electrical stimulation of incoming white-matter fiber tracts. Here, BAF312 administration showed partial restore of cortical neuronal circuit function. The data suggest that BAF312 exerts a neuroprotective effect after crossing the blood-brain barrier independently of peripheral effects on immune cells. Experiments were carried out in accordance with German and EU animal protection law and approved by local authorities (Landesamt für Natur, Umwelt und Verbraucherschutz Nordrhein-Westfalen; 87-51.04.2010.A331) on December 28, 2010.